The Oracle/PeopleSoft case: unilateral effects, simulation models and econometrics in contemporary merger control - Oliver Budzinski; Arndt Christiansen (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
An increasingly important part of contemporary merger control both in the US and the EU is unilateral effects analysis, particularly with regard to oligopolistic mergers. In practice, this requires econometric analyses of past market data and, above all, the construction of simulation models in order to quantify the price effects in each specific case. The review of the merger between the software firms Oracle and PeopleSoft in 2003/04 has been the most important instance of parallel application of these sophisticated economic tools by the EU and US authorities so far. This makes an in-depth study of the case going from the controversial issue of market definition to the specificities of the competitive assessment worthwhile. Therefore, we highlight certain similarities as well as (minor) differences between the EU and US proceedings. Interestingly, despite serious initial concerns the transaction was not blocked nor even required to be modified in the two jurisdictions. We derive a number of interesting insights and, in particular, point out problems and lessons associated with the use of sophisticated economic tools in contemporary merger control. In addition to case-specific factors, the major insights encompass the continued relevance of market definition, the need to accompany predictive economic evidence with compatible reasoning and the benefits of including the economics of dynamic and evolutionary competition.
Keywords: F02; K21; L41; 330; Merger control; unilateral effects; econometric analysis; simulation models; market definition; Fusionskontrolle; Relevanter Markt; Wettbewerb; Simulation; Softwareindustrie; EU-Staaten; USA